Removal of Foodborne Pathogen Biofilms by Acidic Electrolyzed Water - Han, Qiao; Song, Xueying; Zhang, Zhaohuan; Fu, Jiaojiao; Wang, Xu; Malakar, Pradeep K.; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2017)
Biofilms, which are complex microbial communities embedded in the protective extracellular polymeric substances (EPS), are difficult to remove in food production facilities. In this study, the use of acidic electrolyzed water (AEW) to remove foodborne pathogen biofilms was evaluated. We used a green fluorescent protein-tagged Escherichia coli for monitoring the efficiency of AEW for removing biofilms, where under the optimal treatment conditions, the fluorescent signal of cells in the biofilm disappeared rapidly and the population of biofilm cells was reduced by more than 67%. Additionally, AEW triggered EPS disruption, as indicated by the deformation of the carbohydrate C-O-C bond and deformation of the aromatic rings in the amino acids tyrosine and phenylalanine. These deformations were identified by EPS chemical analysis and Raman spectroscopic analysis. Scanning electron microscopy (SEM) images confirmed that the breakup and detachment of biofilm were enhanced after AEW treatment. Further, AEW also eradicated biofilms formed by both Gram - negative bacteria (Vibrio parahaemolyticus) and Gram - positive bacteria (Listeria monocytogenes) and was observed to inactivate the detached cells which are a potential source of secondary pollution. This study demonstrates that AEW could be a reliable foodborne pathogen biofilm disrupter and an ecofriendly alternative to sanitizers traditionally used in the food industry.